Pengaruh Model Project Based Learning (PjBL) terhadap Hasil Belajar Siswa Kelas 2 Sekolah Dasar pada Materi Operasi Hitung Perkalian dan Pembagian - Amalia Khoirun Nisa; Maulida Zulfa Faradilla; Rizki Yulia Nanda; Nur Wiji Sholikin (IEC: Journal of Educational Innovation, 2026)
This study aimed to examine the effect of implementing the Project Based Learning (PjBL) model on the mathematics learning outcomes of second-grade students at SD Integral Hidayatullah Probolinggo in the topic of multiplication and division operations. The study employed a quantitative approach using a one-group pre-test–post-test experimental design. Data were collected through pre-test and post-test instruments to measure students' learning outcomes before and after the implementation of the PjBL model. Data analysis was conducted using IBM SPSS Statistics, including descriptive statistical analysis, the Kolmogorov–Smirnov and Shapiro–Wilk normality tests, and the Mann–Whitney U non-parametric test because the data did not meet the assumption of normality. The analysis yielded an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), indicating a statistically significant difference between the pre-test and post-test results. The findings suggest that the implementation of the Project Based Learning model had an effect on students' mathematics learning outcomes in multiplication and division operations. Therefore, the PjBL model can serve as an alternative instructional approach to promote active, contextual, and student-centered learning through project-based activities.